Two-stage and sequential estimation of parameter N of binomial distribution when p is known. Issue 4 (1st October 2016) - De, Shyamal K.; Zacks, Shelemyahu
ABSTRACT: In this article, we propose two-stage and purely sequential procedures to construct bounded width and prescribed proportional closeness confidence intervals for the unknown parameter N of B ( N, p ) distribution where the parameter p is assumed to be known. The exact distributions of the stopping variables and the estimators of N at stopping are derived for all cases. The coverage probabilities of the proposed interval estimator are computed exactly and are shown to be nearly the same as the prescribed level.